2017
DOI: 10.1007/s11060-017-2650-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of in silico mathematical modeling for glioblastoma: a critical review

Abstract: Glioblastoma remains a clinical challenge in spite of years of extensive research. Novel approaches are needed in order to integrate the existing knowledge. This is the potential role of mathematical oncology. This paper reviews mathematical models on glioblastoma from the clinical doctor's point of view, with focus on 3D modeling approaches of radiation response of in vivo glioblastomas based on contemporary imaging techniques. As these models aim to provide a clinically useful tool in the era of personalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Further advances in radiogenomics could be of great help in the near future, especially in the follow-up phase of GBM when repeated biopsies or extensive genomic and transcriptomic analysis are not possible. In addition, 3D models that simulate response to radiotherapy have also been developed and validated in small number of patients, based on modern imaging techniques [189].…”
Section: Emerging Novel Technologies and Approaches For Studying Invasive Gbmmentioning
confidence: 99%
“…Further advances in radiogenomics could be of great help in the near future, especially in the follow-up phase of GBM when repeated biopsies or extensive genomic and transcriptomic analysis are not possible. In addition, 3D models that simulate response to radiotherapy have also been developed and validated in small number of patients, based on modern imaging techniques [189].…”
Section: Emerging Novel Technologies and Approaches For Studying Invasive Gbmmentioning
confidence: 99%
“…Individual-cell-based models are in general more suitable to describe in vitro experiments, genotype-phenotype relations, local interactions of heterogeneous populations and migration mechanisms. A comprehensive overview of the mathematical models developed for GB progression and therapy response from the clinical perspective and personalized medicine are summarized in 31 . In addition, a thorough review summarizing major studies related to GB invasion can be found in Alfonso et al .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, computational models provide a tool to simulate ‘what-if’ scenarios such as up/downregulation of key components that could be targeted. In silico clinical trials, recently baptized phase i trials [162], aid in matching the “right drug to the right patient” [13, 18, 163]. A key idea is the shift from real-world clinical trial testing a single treatment option on many, mostly unselected, patients to first test in silico several treatment options, both approved or repurposed, for each individual patient.…”
Section: Discussionmentioning
confidence: 99%